1998
DOI: 10.1002/chin.199812016
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Synthesis and Properties of CdLn2X4 (X: S, Se, Te) and CdLn4S7 Chalcogenides.

Abstract: Synthesis and Properties of CdLn 2 X 4 (X: S, Se, Te) and CdLn 4 S 7 Chalcogenides.-The formation of the ternary compounds CdLn 2 X 4 (I) and CdLn 4 X 7 (II) in the CdX-Ln 2 X 3 systems is established. Single crystal XRD studies indicate that compounds (I) of the cerium subgroup crystallize in the cubic system (Th 3 P 4 -type), compounds (I) of the yttrium subgroup have a spinel-type structure, and that compounds (II) are isostructural to Y 5 S 7 . The compounds CdLn 2 S 4 (Ln: La, Ce, Pr, Nd, Sm, Gd, Tb) prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…22,23 CdLn 2 S 4 (Ln = Ho, Er, Tm, Yb) and CdLn 2 S 4 (Ln = Dy, Ho) have been registered as suitable semiconductors with band gap equal to or greater than 2 eV according to available experimental data. 24,25 In these spinels, the cationic distribution and arrangement contribute to the formation of magnetic sublattices resembling pyrochlores. An appropriate choice of exchange-correlation functional is critical in density functional theory (DFT) calculations to probe magnetically frustrated structures 26 accurately.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…22,23 CdLn 2 S 4 (Ln = Ho, Er, Tm, Yb) and CdLn 2 S 4 (Ln = Dy, Ho) have been registered as suitable semiconductors with band gap equal to or greater than 2 eV according to available experimental data. 24,25 In these spinels, the cationic distribution and arrangement contribute to the formation of magnetic sublattices resembling pyrochlores. An appropriate choice of exchange-correlation functional is critical in density functional theory (DFT) calculations to probe magnetically frustrated structures 26 accurately.…”
Section: Introductionmentioning
confidence: 99%
“…In compounds such as Dy 2 Ti 2 O 7 and Ho 2 Ti 2 O 7 , the specific ferromagnetic coupling and spin directions are crucial in generating spin ice properties. These materials exhibit spin orientations that resemble the position of hydrogen atoms in water ice, giving rise to a spin ice-like behavior. This similarity has attracted significant attention in the study of transition-metal-based spinels like CdFe 2 O 4 and ZnCr 2 O 4 due to their geometric frustration. , Still, the existence of relatively potent spin–lattice couplings within the transition-metal-based materials is frequently directed to a decisive state in which structural transitions and magnetic ordering are coupled. , CdLn 2 S 4 (Ln = Ho, Er, Tm, Yb) and CdLn 2 S 4 (Ln = Dy, Ho) have been registered as suitable semiconductors with band gap equal to or greater than 2 eV according to available experimental data. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This family of compounds had been prepared and recognized for the first time by Suchow and Stemple [11]. In some studies on electronic properties [12,13], these spinels were reported as insulating materials with band gap values that are equal and greater to 2 eV, highlighting their potential for device applications like LED, photoconductors, photoelectrochemical solar cells and photocatalysis [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…16,17 The structural and magnetic characteristics of semiconductors spinels like CdLn 2 S 4 (Ln = Yb, Tm, Er, Ho) and CdLn 2 Se 4 (Ln = Ho, Dy) have been investigated experimentally. 18,19 The magnetic sublattices of these compounds are similar to pyrochlores due to the non-magnetic ions and random free ionic distribution in the lattice. Recently, many spinel structure-based materials such as CdLnSe 4 and CdLnS 4 have been analyzed with geometric infuriation having Fd-3m space group and exhibit basic structure analogous to pyrochlores in which magnetic ions composition form a chain of corner-assigned tetrahedra that is totally distinct coordination of RE ions.…”
mentioning
confidence: 99%